2012
DOI: 10.1097/imi.0b013e3182542ab3
|View full text |Cite
|
Sign up to set email alerts
|

Robotic En Bloc First-Rib Resection for Paget-Schroetter Disease, a Form of Thoracic Outlet Syndrome Technique and Initial Results

Abstract: Objective First-rib resection is a key component of the treatment of Paget-Schroetter disease. There are many controversies regarding the management of this disease. We report a safe, effective, minimally invasive robotic transthoracic approach for resection of the first rib. Methods Over an 8-month period, five patients underwent robotic first-rib resection. Preoperative assessment included physical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 19 publications
(19 reference statements)
2
28
0
1
Order By: Relevance
“…Surgical approaches to first rib resection may be transthoracic, transaxillary, supraclavicular, infraclavicular, or thoracoscopic [9, 10]. However, these approaches are typically associated with incomplete resection of the most medial portion of the first rib and neurovascular complications [11]. Theoretically, a minimally invasive transthoracic approach can obviate these problems, enabling complete resection of the offending portion of the first rib without neurovascular complication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical approaches to first rib resection may be transthoracic, transaxillary, supraclavicular, infraclavicular, or thoracoscopic [9, 10]. However, these approaches are typically associated with incomplete resection of the most medial portion of the first rib and neurovascular complications [11]. Theoretically, a minimally invasive transthoracic approach can obviate these problems, enabling complete resection of the offending portion of the first rib without neurovascular complication.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, a minimally invasive transthoracic approach can obviate these problems, enabling complete resection of the offending portion of the first rib without neurovascular complication. Gharagozloo et al and Martinez et al, respectively, reported successful results of robotic en bloc first rib resection for TOS treatment via transthoracic and transaxillary approaches [9, 11]. Gharagozloo et al and Martinez et al's techniques were only bony interventions and as being intrathoracic these need to be lung collapsed and lung complication can be waiting risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At one-year follow-up, all patients maintained patent subclavian veins without any additional intervention. The average length of hospital stay was three days [27]. A later series from this institution evaluated the outcomes of robotic first rib resection for venous TOS in 13 patients and continued to demonstrate similar results with 100% vein patency at six months and a mean post-operative hospital stay of three days.…”
Section: Treatmentmentioning
confidence: 94%
“…Videotorakoskopik TOS cerrahisi uygulamalarına alternatif olarak, Gharagozloo ve arkadaşları 2012 yılında robotik TOS cerrahisini gündeme getirmişler, birinci kostanın mediyal 2/3 kısmının çıkartıldığı ve skalenotomi uyguladıkları 5 Paget-Schroetter olgusunda başarılı sonuçlarını bildirmişlerdir (5).…”
Section: Videotorakoskopik Tos Cerrahisinin Endikasyon Ve Kontrendikaunclassified